Implementation of The 1958 New York Convention in Several Asian Countries: The Refusal of Foreign Arbitral Awards Enforcement on The Grounds of Public Policy - Radjagukguk, Erman (UI Scholars Hub, 2011)
The national character of public policy indicates that the decision is up to the court of national country concerned. Therefore, each country can rule whether public policy and its related issues are part of the country's public policy. Courts atound the world have recognized that Article V of the Convention is discretionary. The courts of Civil Law countries appear to be interpreting public policy broadly. This is quite evident from decisions made by courts in Indonesia, The People's Republic of China, Japan and Korea. The Indonesia Court considered Article V (2) (b) of the New Yourk Convention which states that the court may deny the enforcement of an arbitral award if enforcement would violate public policy of the place of enforcement. In addition, before the enactment of Law No. 30 of 1999 concerning Abitrartion and Alternative Dispute Resolution, the Court referred to Indonesian Supreme Court Regulation No.1 of 1999, which provides that the enofcement of foreign arbitral awards in Indonesia imitatively applies to awards which do not violate public policy order in terms of all underlying principle of the Indonesia legal system and society. In Indonesia, Bakrie Brother v. Trading Corporation of Pakistan Ltd., was the first case in which the indonesia court rejected the enforcement of foreign arbitral awards for the reason of violating public policy